The influence of mechanical engineering on agriculture - Buck, Con Morrison (My University, 1896)
Introduction: To consider the vast progress made in this art and science, we need not go back to the time of the ancient Romans, but only to the old Colonial days. In those days small log-house dotted the not much larger dealings. Not very elegant was the appearance of these houses, although they might be called artistic by the artist of the present day. But those were times when shelter from the storms and protection from the red man were most to be desired. The furniture was plain, home-made, and strong. The large open fire-place lighted the room in the frosty winter twilight, and furnished warmth and means for cooking the food. And the hooks upon the wall hung the trusty old rifle, which serve both as a means of support in supplying food, and a defense against the blood-thirsty Indians.
Citation: Buck, Con Morrison. The influence of mechanical engineering on agriculture. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Ancient Romans; Colonial days; Arts; Sciences; Indians; Theses; Manuscripts (documents)